2007
DOI: 10.1177/0363546506295939
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Chronic Achilles Tendon Rupture with the use of Interposed Tissue between the Stumps

Abstract: Interposed tissue between the tendon stumps is suitable for repair of chronic Achilles tendon rupture if preoperative MRI shows a thickened fusiform-shaped Achilles tendon with diffuse intratendinous high-signal alterations throughout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…No failure of the FHLT transfer occurred during the follow-up period. Also all previous studies with FHLT transfer, despite the single or double incision technique, preserving or not the scar tissue, have shown very low failure rates [5,6,8,9,12,[16][17][18].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…No failure of the FHLT transfer occurred during the follow-up period. Also all previous studies with FHLT transfer, despite the single or double incision technique, preserving or not the scar tissue, have shown very low failure rates [5,6,8,9,12,[16][17][18].…”
Section: Discussionmentioning
confidence: 96%
“…Some authors propose the complete excision of the degenerative Achilles due to better pain relief [4]. In recent series, however, preservation of the fibrous scar tissue has been suggested to make the tendon length assessment easier and the scar tissue is thought to work as a scaffold for the transferred FHLT [5,6,8].In fact, this scar tissue has been shown to have the capacity to form a tendon like repair tissue [16][17][18]. In our study, the tendon stumps were preserved, and possible deficits were bridged with single strand of FHL tendon only.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, fibrous scar tissue of AT stumps was preserved to restore some thickness with suture on the FHL transfer. Preserving this interposition scar tissue between tendon stumps has been shown to have the capacity to form tendon-like repair tissue, and previous studies concluded that it is suitable for repairing chronic AT ruptures [20,29]. Similarly, in a recent study, Lee et al showed on histological examination of fibrous scar stump biopsies that this tissue was composed of thick collagen fibers running parallel to the tendon axis with highly cellular fibrovascular tissue, altogether improving tendon healing [15].…”
Section: Discussionmentioning
confidence: 98%
“…Percutaneous tendon repair surgery is preferred in acute and small or middle dimension injuries [14]. Scar tissue has been proposed to be used in chronic lesions for direct repair in patients with tendinosis [15]. Direct repair is a primary option (eventually associated with reinforcement plasty) but in chronic cases is not always possible and grafts techniques should be required.…”
Section: Discussionmentioning
confidence: 99%